On the Derivation of the Equations of Gravitation and Electrodynamics from the Generalized Least Action Principle and the Nonrelativistic Models of the Universe - Vedenyapin, V.V.; Fimin, N.N.; Russkov, A.A.; Voronina, M.Yu. (Journal of Vibration Testing and System Dynamics, 2026)
Of the Maxwell and Einstein equations in the framework of the Vlasov--Maxwell--Einstein equations from the classical, but more general principle of least action. The resulting derivation of the Vlasov--type equations gives the Vlasov--Einstein equations different from those proposed earlier. A method is proposed for the transition from kinetic equations to hydrodynamic--type equations. In the case of Hamiltonian mechanics, the transition to the Hamilton--Jacobi equation from the hydrodynamic consequences of the Liouville equation is possible, as was done already in quantum mechanics. Thus, in the nonrelativistic case, we obtain the Milne--McCrea{--type} solutions.